Bisnis Model Ruang Baca Upt Perpustakaan Bung Karno X Kedai Kopi - Widadari, Ningsih; Arisyahidin, Arisyahidin (Universitas Islam Kadiri, 2025)
The quality of a nation is determined by its intelligence and knowledge, while intelligence and knowledge are generated by how much knowledge it obtains. Knowledge is obtained from information which acquire verbally or in writing. Literacy skills are one of the most important needs for individuals to be compete in the 21st Century. The literacy rate of a nation is directly shows to the country’s people quality. The extent of a person's interest in reading books influences a person's views, thought patterns and behavior. UPT Perpustakaan Proklamator Bung Karno has a bulk loan service as a means of information for users who are geographically far from the library to obtain permanent information so that they can achieve the vision and mission of the library to improve reading culture in the community by lending books in bulk to institutions, agencies and reading parks so that they can used optimally. Bulk loan's work results report from year to year states that the highest number of service users are students with up to 80% of all users. This case was inspiring the author to conduct research to design a business model as an innovation for equal distribution of bulk loan services so that they can reach people from various circles and backgrounds. The results of the research succeeded in formulating a business canvas model for Reading Rooms in Coffee Shops, which is a collaboration between the Bulkloan service of the UPT Perpustakaan Proklamator Bung Karno as a provider of book collections and the Coffee shops as providers of space and management of reading rooms